Functional Zeolitic Imidazolate Framework for Robust l‐Deoxyribozyme‐Based Therapy. Issue 47 (10th October 2022) - Tan, Kaiyue; Zhang, Qingqing; Wang, Qing; Gong, Xue; Yu, Shanshan; Li, Ruomeng; Liu, Xiaoqing; Wang, Fuan
Abstract: Programmable chiral biocatalysis represents a promising therapeutic strategy for its high stereospecific control over various biotransformations (e.g., chiral Aβ isomerization) of living entities yet is rarely explored. With an extraordinary resistance to nuclease digestion, the non‐natural left‐handed deoxyribozyme (l ‐DNAzyme) therapy is constrained by inefficient delivery/release and insufficient cofactors supply. Herein, an efficient adenosine triphosphate (ATP)‐stimulated disassembly of l ‐histidine (l ‐His)‐integrated ZIF‐8 (l ‐His‐ZIF‐8) is reported for sustaining the l ‐DNAzyme‐amplified photodynamic therapy. This self‐sufficient l ‐therapeutic platform can intelligently release the l ‐DNAzyme probe and simultaneously supply l ‐His DNAzyme cofactors via endogenous ATP. Then, the intrinsic microRNA‐21 catalyzes the generation of robust l ‐DNAzyme via the catalytic hybridization reaction for activating the photosensitizer with multiplied guaranteed therapeutic operation. This l ‐therapeutic strategy opens up great prospects for more precise diagnosis and customized gene silencing‐based therapy. Abstract : The adenosine triphosphate (ATP)‐stimulated disassembly of functional l ‐His‐ZIF‐8 NPs is reported for sustaining the left‐handed deoxyribozyme (l ‐DNAzyme)‐amplified photodynamic therapy via the intelligent release of l ‐DNAzyme probes and the simultaneous supply of l ‐histidine cofactors via endogenous ATP and microRNA.